AB0279 High rate of disability pension in chilean rheumatoid arthritis patients without access to biologics. hospital padre hurtado experience. (15th June 2017) - Vodnizza, SE Ibáñez; Valenzuela, O; Silva, F; Villar, MJ
Abstract : Background: Until the year 2016, most of the Chilean rheumatoid arthritis patients in the public health system did not have acces to biologic treatment. Now the access is limited to those with high disease activity (DAS 28 >5.1). Objectives: Our main objective was to evaluate the rate of patients benefited by disability pension within the group of rheumatoid arthritis patients seen in our center, before the introduction of biologic treatment for those with high disease activity. Our secondary objective was to estimate the association between having a disability pension and the characteristics of the patients. Methods: Consecutive rheumatoid arthritis patients (according to the ACR 2010 criteria), 18 years old or older, that attended to our rheumatology consult between September and December of 2015, were included. Patients with other types of pensions (retirement) were excluded. Information about work status, gender, age, years since diagnosis, medications used, DAS 28 ESR and its variables was collected. Results: 104 patients were included. 38.5% had a disability pension. We found significant differences between the patients with and without disability pensions for age, years since diagnosis, tramadol use, the number of tender joints, the number of swollen joints and DAS 28 ESR (Table 1 ). After multivariate logistic regression, age (OR 1, 95% CI 1.02–1.15), tramadol use (OR 0.3, 95% CI 0.08–0.92) and the number of swollen joints (OR 1.4, 95% CI 1–1.96) continued to be significantly associated. Conclusions: Near forty percent of our rheumatoid arthritis patients, that did not have access to biologic treatment, were being paid a disability pension, and this condition was significatly associated with more years of age, tramadol use, and the number of swollen joints. The mean DAS 28 ESR in the patients with disability pension was 5. The limit of a DAS 28 >5.1 to authorize the use of biologic treatment possibly will not help to reduce the rate of patients with disability pension in our group. Disclosure of Interest: None declared